Thiamine antagonists trigger p53-dependent apoptosis in differentiated SH-SY5Y cells - Sergiy Chornyy (Nature Portfolio, 2017)
Abstract Accumulating evidences suggest that p53 is a key coordinator of cellular events triggered by oxidative stress often associated with the impairment in thiamine metabolism and its functions. However, there are limited data regarding the pursuant feedback between p53 transactivation and thiamine homeostasis. Impairment in thiamine metabolism can be induced experimentally via interference with the thiamine uptake and/or inhibition of the thiamin pyrophosphate–dependent enzymes using thiamine antagonists - amprolium (AM), oxythiamine (OT) or pyrithiamine (PT). We found that exposure of neuronally differentiated SH-SY5Y cells to AM, OT and PT triggered upregulation of p53 gene expression, post-translational modification of p53 via phosphorylation and activation of p53 DNA-binding activity. Phosphorylation of p53 at Ser20 was equally efficient in upregulation of thiamine transporter 1 (THTR1) by all antagonists. However, induction of the expressions of the pyruvate dehydrogenase E1 component subunit beta (PDHB) and oxoglutarate dehydrogenase (OGDH) required dual phosphorylation of p53 at Ser9 and Ser20, seen in cells treated with PT and OT. Moreover, pretreatment of the cells with a decoy oligonucleotide carrying wild-type p53-response element markedly attenuated OT-induced THTR1, PDHB and OGDH gene expression suggesting an important role of p53 in transactivation of these genes. Finally, analysis of gene and metabolic networks showed that OT triggers cell apoptosis through the p53-dependent intrinsic pathway.